Hybrid biological, electron beam and zero-valent nano iron treatment of recalcitrant metalworking fluids. (15th April 2016) - Thill, Patrick G.; Ager, Duane K.; Vojnovic, Borivoj; Tesh, Sarah J.; Scott, Thomas B.; Thompson, Ian P.
Abstract: Hybrid approaches for the remediation and detoxification of toxic recalcitrant industrial wastewater were investigated. The focus was waste metalworking fluid, which was selected as a representative model of other waste streams that are toxic, recalcitrant and that require more sustainable routes of safe disposal. The hybrid approaches included biodegradation, electron beam irradiation and zero-valent nano iron advanced oxidation processes that were employed individually and in sequence employing a factorial design. To compare process performance operationally exhausted and pristine metalworking fluid were compared. Sequential hybrid electron beam irradiation, biological, nanoscale zero-valent iron and biological treatment lead to synergistic detoxification and degradation of both recalcitrant streams, as determined by complementary surrogates and lead to overall improved COD removal of 92.8 ± 1.4% up from 85.9 ± 3.4% for the pristine metalworking fluid. Electron beam pre-treatment enabled more effective biotreatment, achieving 69.5 ± 8% (p = 0.005) and 24.6 ± 4.8% (p = 0.044) COD reductions. Graphical abstract: Highlights: Hybrid sequential treatment improved COD removal and toxicity surrogates. E-beam and zerovalent nano iron treatment complemented biological treatment. MWF streams could be bio-treated at higher COD loads after irradiation.